RuO2 nanorods decorated CNTs grown carbon cloth as a free standing electrode for supercapacitor and lithium ion batteries. (5th December 2019) - Asim, Sumreen; Javed, Muhammad Sufyan; Hussain, Shahid; Rana, Masud; Iram, Fozia; Lv, Dingding; Hashim, Muhammad; Saleem, Muhammad; Khalid, Muhammad; Jawaria, Riffat; Ullah, Zaka; Gull, Nafisa
Abstract: Engineering carbon-based nanostructures, including synthesis, structural designing, and characterization between carbon and active nanomaterials, possesses enormous potential for enabling exceptional electrochemical characteristics and fundamental breakthroughs. Here, we reported RuO2 nanorods (RuO2 -NRs) decorated CNTS grown carbon cloth (CNTS-CC) via simple single step CVD and annealing process, as an excellent combination having advantages of the supercapacitors (SCs) and Li-ion batteries (LIBs). A number of characterizations, including scanning electron microscopy, X-ray photoelectron spectroscopy, and X-ray diffraction measurements affirm that RuO2 -NRs are consistently covering the surface of CNTS-CC. The Brunauere Emmette Teller analysis displays that the fabricated architecture holds a well organized 3D interconnected hierarchically micro-mesoporous network that simultaneously facilitates rapid electron transfer and ion diffusion. Furthermore, the electrochemical performance revealing that the RuO2 -CNTS-CC has outstanding Li-ion storage potential, including impressive rate capability, large specific capacity and excellent cyclic stability. For supercapacitor application, it is found that RuO2 -CNT-CC holds an admirable specific capacitance that can maintain up to 97% after 10, 000 cycles. The compatible and inexpensive preparation strategy presented here can contribute as a dynamic methodology towards the advancement of efficient hybrid devices. Graphical abstract: Image 1